2016
DOI: 10.4238/gmr.15028114
|View full text |Cite
|
Sign up to set email alerts
|

Common variant rs7579169 is associated with preeclampsia in Han Chinese women

Abstract: ABSTRACT. As a heterogeneous group of disorders in pregnancy, many genetic factors are involved in the development of preeclampsia. The single nucleotide polymorphism (SNP) rs7579169, located on chromosome 2q14.2, has been shown to be associated with pregnancyinduced hypertension in Europeans. In this study, we examined whether the SNP rs7579169 is associated with the susceptibility to preeclampsia through a case-control research model in Han Chinese women. Genotypes of 145 patients with preeclampsia and 150 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…One study identified two loci (rs7579169 and rs12711941) near the inhibin beta B gene that satisfied the genome‐wide significance threshold, but the results could not be replicated in two cohorts from Norway and Finland. Subsequent case–control studies in European and Chinese women have shown a significant association between the SNP rs7579169 and PE.…”
Section: Discussionmentioning
confidence: 99%
“…One study identified two loci (rs7579169 and rs12711941) near the inhibin beta B gene that satisfied the genome‐wide significance threshold, but the results could not be replicated in two cohorts from Norway and Finland. Subsequent case–control studies in European and Chinese women have shown a significant association between the SNP rs7579169 and PE.…”
Section: Discussionmentioning
confidence: 99%
“…Since HDP is thought to be induced by a two-step mechanism, the pathology of HDP likely originates in a background of placental dysfunction (Chen et al, 2017). Many causes of HDP have been reported, and HDP is believed to be a multifactorial genetic disorder (Guo et al, 2016). The main mechanisms involved in HDP are believed to include damage to endothelial cells, thrombotic tendencies, placenta dysfunctions, and oxygen deficiencies (Gu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among calpains with a nonspecific catalytic subunit, two types (μ-calpain and m-calpain) have been the subjects of advanced functional analysis (Goll et al, 2003). Notably, μ-calpain and m-calpain share the same regulatory subunit, CAPNS1, but differ in their catalytic subunit, with μ-calpain employing CAPN1, and m-calpain employing CAPN2 (Guo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%